Uncommon ground : living faithfully in a world of difference - Keller, Timothy, 1950-; Inazu, John D. (Thomas Nelson, 2020)
How can Christians today interact with those around them in a way that shows respect to those whose beliefs are radically different but that also remains faithful to the gospel? Timothy Keller and John Inazu bring together illuminating stories - their own and from others - to answer this vital question. Uncommon Ground gathers an array of perspectives from people thinking deeply and working daily to live with humility, patience, and tolerance in our time.